Fat and Happy: Profiling Mosquito Fat Body Lipid Storage and Composition Post-blood Meal - Pinch, Matthew; Mitra, Soumi; Rodriguez, Stacy D.; Li, Yiyi; Kandel, Yashoda; Dungan, Barry; Holguin, F. Omar; Attardo, Geoffrey M.; Hansen, Immo A. (Frontiers in Insect Science, 2021)
The fat body is considered the insect analogue of vertebrate liver and fat tissue. In mosquitoes, a blood meal triggers a series of processes in the fat body that culminate in vitellogenesis, the process of yolk formation. Lipids are stored in the fat body in specialized organelles called lipid droplets that change in size depending on the nutritional and metabolic status of the insect. We surveyed lipid droplets in female Aedes aegypti fat body during a reproductive cycle using confocal microscopy and analyzed the dynamic changes in the fat body lipidome during this process using LC/MS. We found that lipid droplets underwent dynamic changes in volume after the mosquito took a blood meal. The lipid composition found in the fat body is quite complex with 117 distinct lipids that fall into 19 classes and sublcasses. Our results demonstrate that the lipid composition of the fat body is complex as most lipid classes underwent significant changes over the course of the vitellogenic cycle. This study lays the foundation for identifying unknown biochemical pathways active in the mosquito fat body, that are high-value targets for the development of novel mosquito control strategies.